Performance Efficiency of Municipality Staff According to Alcoholic Control Act B.E.2551 from Distributors’ Perspectives in Thung Song Municipality, Nakhon Si Thammarat - Sriboon, Rasamee; Yotharak, Damrong; Sudsomboon, Sudarat; Timglub, Kanoknat; Samerpark, Saithong; Rattanamusik, Phongphan (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
This research employed a mixed-method design which aimed to examine roles of municipality staff, procedures, problems and suggestions relevant to promotion of local alcohol control and their performance efficiency in compliance with Alcohol Control Act B.E. 2551 as perceived by distributors in Thung Song Municipality. Qualitative data were obtained through in-depth interviews with 10 municipality officers who were in charge of alcohol control and 10 local distributors. Quantitative data were collected from 120 distributors. Statistical analyses of percentages, mean, standard deviation, one-way ANOVA, Least Significant Difference (LSD) and f-test were conducted. Results revealed that (1) the roles of staff in controlling the alcohol were not practical. (2) Notify that ask for cooperation from all department of district officer, (3) distributors are not aware of law related to alcohol as they lack educational support. And (4) their performance efficiency was rated as “good”. One-way ANOVA analysis revealed that age and educational background affected differences in their perceptions of the staff performance at .05 level of statistical significance.